Surgical intensive care unit: essential for good outcome in major abdominal surgery? - Linke, Georg R.; Mieth, Markus; Hofer, Stefan; Trierweiler-Hauke, Birgit; Weitz, Jürgen; Martin, Eike; Büchler, Markus W. (Langenbeck's archives of surgery, 2011)
Surgical intensive care units (ICU) play a pivotal role in perioperative care of patients undergoing major abdominal surgery. Differences in quality of care provided by medical staff in ICUs may be linked to improved outcome. This review aims to elucidate the relationship between quality of care at various ICUs and patient outcome, with the ultimate aim of identifying key measures for achieving optimal outcome.
Gesehen am 14.09.2022